Association between variant alleles of major histocompatibility complex class II regulatory genes and nasopharyngeal carcinoma susceptibility. Issue 6 (November 2020) - Zhou, Ping; Liu, Sha; Ji, Nan-Nan; Zhang, Shuang; Wang, Peng; Lin, Bing; Yang, Ping; Lin, Xian-Tao; Cai, Yi-Zheng; Wang, Zi-Ming; Zhou, Han; Sun, Shi-Yao; et al.
Abstract : Major histocompatibility complex ( MHC ) class II regulatory genes play a paramount role in immune response that can exert a predominant influence on clinical outcome of Epstein–Barr virus infection consistently assumed as the main pathogenetic factor for nasopharyngeal carcinoma. To elucidate the relationship between allelic variants of MHC class II regulatory genes and susceptibility to nasopharyngeal carcinoma, a total of 28 polymorphic loci at MHC class II regulatory genes, involving CIITA, CREB1, RFX family genes ( RFX5, RFXAP, and RFXANK ), and NFY family genes (NFYA, NFYB, and NFY C), were genotyped by multiplex SNaPshot minisequencing in 137 patients with nasopharyngeal carcinoma and 107 healthy controls from the southern Chinese population. Allelic analysis disclosed that rs7404873, rs6498121, rs6498126, and rs56074043 shared correlations with nasopharyngeal carcinoma ( P trend < 0.05). Further, rs6498126 on CIITA was independently associated with the risk of developing nasopharyngeal carcinoma (CC vs. GG, odds ratio: 7.386, 95% confidence interval: 1.934–28.207, P trend < 0.01). Conversely, rs7404873 on CIITA and rs56074043 on NFYB manifested epistatic interaction to decreased susceptibility of nasopharyngeal carcinoma (rs7404873, TT vs. GG, odds ratio: 0.256, 95% confidence interval: 0.088–0.740, P trend < 0.05; rs56074043, AA vs. AG, odds ratio: 0.341, 95% confidence interval: 0.129–0.900, P trend < 0.05). Additionally, bioinformatics analysis revealed that the three variants were transcriptional regulatory in function and might impact the expression of nearby genes. The findings suggested genetic variants on MHC class II regulatory genes contributed to nasopharyngeal carcinoma susceptibility and might provide new insights for screening high-risk population. Abstract : Supplemental Digital Content is available in the text.